Influence of eating disorders in young females (Research, Society and Development, 2020)
Eating disorders (ED) represent one of the main public health problems, affecting mainly female adolescents and young adults, culminating in dissatisfaction with body image, search for the ideal body and psychological vulnerabilities. The aim of the study is to analyze evidence in the literature regarding the psychological, social and economic factors in the development of ED in young women. This is an integrative literature review, carried out by searching for original articles, with a limit of 10 years of publication, in Portuguese, English and Spanish, indexed in the databases of Scielo, Pubmed, Lilacs and Scopus. 952 articles were found in the preliminary search and 12 articles were included, after the selection and removal process of duplicate and ineligible articles. It was found that some factors influence the development and aggravation of ED, among them, body dissatisfaction, self-esteem, idealization of thinness, influence of family, friends and media, indiscriminate use of diets, mood, psychological factors ( depression, anxiety, impulsivity and stress), age, socioeconomic levels and racial ethnic factors. It is concluded that the results confirm that dissatisfaction with body image and psychological problems are the ones that most influence the development of ED. Thus, it is emphasized the need to carry out more studies for further clarification on the subject.